납-안티몬 합금을 이용한 304 스테인리스 강의 좌굴 하중 특성 평가 방법 개발 - 김준이 (The Graduate School, Ajou University, 2022)
후쿠시마 원전 사고에서 알 수 있듯이 중대사고에서는 구조물이 고온, 고압 환경에 노출되고, 이로 인해 설계 기준을 초과하는 사고가 발생할 수 있다. 원전에 주로 사용되는 강(steel)은 온도가 증가함에 따라 강도와 강성의 감소로 쉽게 파괴되고, 결국 심각한 사고를 일으키게 된다. 따라서 설계 기준을 초과하는 환경에서 구조물의 거동에 대한 연구가 필요하다. 좌굴은 구조물의 붕괴와 직접적인 관계를 갖고 있어, 중요한 사고 모드(mode)로 고려된다. 특히, 온도 증가에 따른 재료의 기계적 물성 감소는 좌굴 발생을 촉진시키기 때문에 온도 변화에 따른 좌굴 특성 파악이 필수적이다. 그러나 고온 실험은 위험성, 측정의 어려움, 비용 등의 문제점을 갖고 있어 상온에서 모사 재료(simulation material)를 이용한 실험으로 대신하는 연구에 관심이 높아지고 있다. 본 연구에서는 납-안티몬 합금(Pb-Sb alloy)을 이용하여 304 스테인리스 강의 좌굴 및 크리프 좌굴 평가 모델을 개발하고자 한다. 안티몬의 조성을 0에서 15 wt. %까지 변화시키면서 상온(25℃)에서 초고온(1200℃) 영역에서 304 스테인리스 강의 좌굴 하중 예측 모델을 개발하였다. 이를 위해 납-안티몬 합금의 영률을 측정하였다. 납-안티몬 합금은 안티몬의 조성이 증가함에 따라 영률이 증가하는 경향을 확인하였으며, 2.136 – 16.95 MPa의 영률 범위를 갖는 것을 확인하였다. 미세구조 분석을 통해 미세 구조 차이(라멜라 구조 증가)가 영률을 변화시키는 것을 확인하였다. 좌굴 하중은 1.65 MPa(0 wt. % Sb)에서 11.25 MPa(15 wt. % Sb)까지 변화하는 것을 확인하였다. 또한, 초기 변형을 고려한 좌굴 수치해석 모델을 개발하였으며, 실험값과의 오차는 평균 5.37 %였다. 영률과 좌굴 하중 측정 결과를 바탕으로, 정규화 영률의 함수로 표현되는 좌굴 하중 평가 모델을 개발하였다. 개발된 모델의 평균 오차는 4.94 %였다. 추가로, 크리프 좌굴의 평가 모델 개발을 위해 좌굴 시편의 수평 변형률을 이용한 수치해석 모델을 개발하였으며, 평균 오차 15% 이하의 높은 정확도를 갖는 것을 확인하였다. 또한 3 wt. %의 안티몬 조성에 대한 좌굴 및 크리프 좌굴 실험을 수행하였으며, 800 ℃ 304 스테인리스 강의 크리프 좌굴 거동과 비교하였다. 이를 통해 상대 하중 기반의 크리프 좌굴 시간 예측 모델을 개발하였다. 좌굴 시간 예측 결과는 평균 49.64 %의 오차를 보였으나, 전체적인 크리프 특성을 파악하는데 유용하게 사용할 수 있을 것으로 판단된다. In the lesson learned from Fukushima nuclear power plant accident, the beyond design basis accident (BDBA) can be occurred in the severe accident under which structural components are exposed to high pressure and high temperature conditions. The steel, which is widely used in nuclear power plants, is vulnerable to temperature changes because its strength and stiffness weaken at high temperatures. Hence, it is necessary to study the behavior of the structural components under the BDBA conditions. Buckling has been considered as a significant failure mode because it is highly associated with the failure of structures. In particular, it is essential to understand the buckling characteristics according to temperature change because the occurrence of buckling is promoted by the decrease of the mechanical properties of the material at high temperatures. However, there exist danger, difficulties in measurements, and high cost in running experiments under high temperatures. For those reasons, simulation materials have great attention to substitute the high temperature experiments with those in room temperature. In this study, the buckling and creep buckling evaluation model for 304 stainless steel were developed using lead-antimony alloy (Pb-Sb alloy). In this study, the evaluation model for predicting the buckling failure load of 304 stainless steel was developed from 25 to 1200 ℃ The modulus of elasticity of the Pb-Sb alloys was experimentally measured as varying Sb composition. In results, the modulus of elasticity was increased with Sb composition from 2.136 to 16.95 MPa. In addition, the change in the micro-structure (increase of the lamella structure) was attributed to the mechanical property change. The buckling load experimentally measured in this study was varied from 1.65 to 11.25 MPa as increasing Sb composition. Moreover, the numerical model for the buckling load that incorporates the initial bending was also developed and the average error was estimated to be 5.37 % in comparison to the experimental results. The buckling load evaluation model was developed as a function of the normalized modulus of elasticity with the average error of 4.94 %. In addition, the numerical model for estimating creep buckling failure time was developed based on the lateral deflection rate. The average of the model was less than 15 %. Also, the creep buckling tests were performed using Pb-Sb alloys with 3 wt. % Sb composition, and then the results were compared to the creep buckling behaviors of 304 stainless steel at 800 ℃. Finally, the creep buckling evaluation model was developed as a function of relative compressive load. The average error of the model was 49.64 % that seems to be useful to understand the creep buckling behaviors of 304 stainless steel.
학위논문(석사)--아주대학교 일반대학원 :기계공학과,2022. 2
Keywords: 구조 건전; 납-안티몬 합금; 좌굴